Problem Solving Learning Model as a Strategy to Strengthen Critical Thinking in PPKN Subjects at MI Miftahul Ulum Driyorejo Gresik - Intan Wahyu Ramadhani; Agustin, Nurul (Antroposen: Journal of Social Studies and Humaniora, 2025)
The quality of learning greatly determines the learning outcomes of students. Optimal learning outcomes are influenced by the role of teachers in presenting learning activities actively. One of the active learning activities is by using learning strategies with the selection of the right learning model, one of which is the Problem Solving learning model. While the focus of this study is: 1) How to apply the use of the Problem Solving model in PPKn class VI and 2) How to improve students' critical thinking skills in PPKn class VI subjects. This study uses the type of Classroom Action Research (CAR), through three stages, namely, planning, action and observation, and reflection. Data collection techniques in this study use observation, documentation, learning outcome tests, and field notes. While the data analysis used in this study is qualitative and quantitative data analysis. The results of this study indicate that the learning implementation process at MI Miftahul Ulum is in accordance with the rules in Problem Solving learning and there is an increase in students' critical thinking skills through the Problem Solving learning model in PPKn subjects. In cycle I obtained 68.9%, increasing in cycle II with a percentage of 89.6%. The results of improving student learning above are said to be successful and achieve success according to the Minimum Completion Criteria (KKM) which is 75%. It can be concluded that the use of the Problem Solving model can improve students' critical thinking skills through learning outcomes in the PPKn subject of Class VI MI Miftahul Ulum Kesamben Wetan Driyorejo Gresik.